Penerapan Teknik Hypnobreastfeeding untuk Meningkatkan Pengeluaran ASI - Jennatur Rahmah; Fatma Jama; Yusrah Taqiyah; Wan Sulastri Emin (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2026)
This breast milk dam is a condition where there is swelling in the breast, which causes the flow of milk to be obstructed. The breastfeeding mother experiences stress, resulting in a decrease in the hormone oxytocin, which helps release milk from the breast. Technique Hypnobreastfeeding. This is a non-pharmacological technique that utilizes positive affirmations/suggestions to facilitate the production of breast milk. The research aims to determine the Effect of Engineering Hypnobreastfeeding on the expenditure of Breast Milk in Breastfeeding Mothers at the Moncongloe Health Center, Maros Regency. This study employs a one-group pretest-posttest design. The population in this study consisted of 162 individuals from the Moncongloe Community Health Center in Maros District, with a total sample size of 38 respondents. The sampling technique used in this study is purposive sampling. A test was conducted in this study using the Wilcoxon statistical test to compare breastfeeding before and after treatment. The results of this study indicate that there was an effect on milk production before the intervention was administered, with a 47.4% increase, and after the intervention, milk production increased by 86.8%, suggesting a technical influence. hypnobreastfeeding in increasing the milk production of nursing mothers with p-value = 0.00 <0.05. The conclusion of this study's results is that the technique of hypnobreastfeeding is effective in increasing milk production in nursing mothers. Therefore, through this research, it is hoped that the public, especially breastfeeding mothers, can apply this as a method to facilitate breastfeeding without having to take breastfeeding booster drugs/supplements. Through the technique of hypnobreastfeeding, it also has no side effects, so it can be done at any time.